Pulau Jawa: Jejak Penting Islam Awal, Peranan Lembaga dan Tokoh Pendidikan yang Membawa Transformasi - Tuti, Hastuti; Rama, Bahaking; Siraj, Arifuddin; Usman (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
This research reviews the development of Islamic education on the island of Java with a focus on analyzing the initial arrival of Islam, the educational institutions that developed, and the figures who influenced the development of this religious education. The research method uses a historical approach by investigating the history of the beginning of the spread of Islam on the island of Java and its impact on the education system. Data were analyzed qualitatively to identify the role of Islamic educational institutions and key figures in this process. This research seeks to provide an in-depth understanding of the role of history in shaping the Islamic education system on the island of Java, as well as its relevance in the current context of religious education. It is hoped that the findings from this research will provide broader insight into the importance of history in developing Islamic religious education in this region.